Interventional treatment for pulmonary venous stenosis due to fibrosing mediastinitis: a case report - Runfeng Gao; Xulong Yang; Shougang Sun; Hao Hu; Yangyang Yu (Frontiers in Cardiovascular Medicine)
IntroductionFibrosing mediastinitis is a rare syndrome caused by the abnormal proliferation of mediastinal fibrous tissue. It often causes superior vena cava syndrome, bronchial stenosis, pulmonary vascular stenosis, etc.Patient presentationAn elderly male patient presented with intermittent chest tightness, shortness of breath, cough, and large pleural effusion. He was diagnosed with fibrosing mediastinitis through echocardiography, chest CT, and inflammatory indicators. Contrast-enhanced CT and selective angiography showed severe stenosis of multiple branches of bilateral pulmonary veins. The patient is considered to have pulmonary vein stenosis caused by FM, and for further treatment, we performed two interventional therapies at different times. After two operations, the stenosis of bilateral multiple pulmonary veins in this patient has been relieved. Additionally, we also discovered that for pulmonary vein stenosis caused by FM, stent implantation is more effective than balloon dilation.ConclusionThis case report confirmed that interventional treatment for pulmonary vein stenosis is safe and effective. This study also provides a potential treatment approach for pulmonary vein stenosis resulting from fibrosing mediastinitis.